Current concepts review - fractures of the shaft of the humerus - Gradu, G; Jupiter, J B (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2013)
Fractures of the shaft of the humerus are common injuries. Historically, the treatment of choice has been functional bracing. Recent technical advances such as angular stable plate and nail constructs lead to a shift in the treatment algorithm for this type of fracture. Surgical treatment is recommended in high grade open fractures, multilevel injury, polytrauma patients, nerve and serious vascular injuries, pathological fractures, and delayed or nonunions. This article aims to describe the published scientific data and current treatment modalities most suitable for each type of fracture.
Keywords: Humans; Fracture Fixation, Internal; pooperační péče; Fracture Healing; Postoperative Care; hojení fraktur; fraktury humeru; polytrauma; Multiple Trauma; Bone Plates; Bone Nails; vnitřní fixace fraktury; kostní destičky; kostní hřeby; Humeral Fractures; lidé